Experimental Assessment on the Coupling Effect of Mixing Length and Methane-Ammonia Blends on Flame Stability and Emissions - Marwan Abdullah; Thibault F. Guiberti; Radi A. Alsulami (Energies, 2023)
Lean premixed combustion mode has become attractive for utilization in industrial gas turbines due to its ability to meet strict emissions regulations without compromising engine efficiency. In this combustion mode, the mixing process is the key player that affect the flame structure and stability, as well as the generated emissions. Many studies have investigated the aspects that influence premixed flames, including the effects of turbulence, combustor geometry, and level of partial premixing, while mostly using conventional natural gas fuel represented by methane. Recently, ammonia, a sustainable energy source, has been considered in gas turbines due to its carbon-free fuel producing no CO2. Utilizing 100% ammonia or a blend of methane and ammonia alters the combustion performance of a premixed flame due to the variation associated with the physical and chemical properties of ammonia. Thus, investigating the coupling between blend ratios and mixing length of methane-ammonia on flame stability and emissions is an essential step toward implementing ammonia in industrial gas turbines. In this study, the influence of various methane-ammonia blends, from 0 (pure methane) to XNH3 = 75%, and mixing lengths on the flame performance were studied. The mixing length was altered by delaying the injection (i.e., partially premixing) of the ammonia while using a fixed injection location for the reference methane-air mixture. This was done by using three fuel ports located at three different heights upstream of the combustion chamber. The results showed that the flame stability is negatively influenced by increasing (decreasing) ammonia fraction (mixing length ratio) and is more sensitive to the ammonia fraction than to the mixing length. At a constant equivalence ratio, the CO and NOx performances improved positively by increasing the ammonia volume fractions (especially at XNH3 = 75% compared to XNH3 = 25% and 50%) and the mixing length.